Pemanfaatan Teknologi Informasi Dan Komunikasi Dalam Pembelajaran SMA Negeri 3 Gunungsitoli - Yadi, Supriyadi Zebua; Sofe Priaman Mendrofa; Nefardin Lase (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
One way to spread learning messages and information is learning media. Well-designed learning media helps students understand and understand the subject matter. With globalization and advances in information technology today, learning media is increasingly advanced. Information and Communication Technology (ICT) as a learning tool is needed. ICT-based media require special skills, but this does not mean they should be avoided or abandoned. Information technology (ICT)-based educational resources can include the internet, intranet, cellphones, and CDs/Flash Disks. In order to remain relevant with the increasingly rapid dynamics of change triggered by technological advances, learning patterns must be changed. By using a descriptive model, this research analyzes and shows how information and communication technology is used in learning at SMAN 3 Gunungsitoli. According to research conducted, the teacher's paradigm in using information and communication technology in learning is still limited to the use of information technology-based computer media as presentation material during the learning process. The need for technology in education is nothing new; Technology can be used to build innovative and fun students.  It has been proven that this use has a great influence on how smoothly the learning process goes.